125k views
3 votes
-x+7= -6x-13 how do you solve it

User Allenh
by
5.6k points

2 Answers

2 votes

Answer:

-4=x

Explanation:

Okay, let's do this step-by-step for the best results!

We need to make sure that common variables can be put together first. If you did not know this, look at PEMDAS.

-x+7=-6x-13

We need to add -x and -6x together. If we do that then you would get,

7=-5x-13

Let's add 13 to 7 now.

20=-5x

Lets divide -5 with 20.

-4=x

I hope this helped!

User Integrating Stuff
by
5.5k points
4 votes

Answer:


\boxed{ \bold{ \huge{ \boxed{ \sf{x = - 4}}}}}

Explanation:


\sf{ - x + 7 = - 6x - 13}

Move 6x to left hand side and change it's sign


\dashrightarrow{ \sf{ - x + 6x + 7 = - 13}}

Move 7 to right hand side and change it's sign


\dashrightarrow{ \sf{ - x + 6x = - 13 - 7}}

Collect like terms


\dashrightarrow{ \sf{ 5x = - 13 - 7}}

Calculate


\dashrightarrow{ \sf{5x = - 20}}

Divide both sides by 5


\dashrightarrow{ \sf{ (5x)/(5) = ( - 20)/(5) }}

Calculate


\dashrightarrow{ \sf{x = - 4}}

Hope I helped!

Best regards! :D